Hubungan Penerimaan Mahasiswa Komunikasi Digital dan Media Pada ChatGPT dan Penggunaannya Dalam Penyelesaian Tugas Praktikum Content Analysis - Simanjuntak, Egalita Fany Adlia; Hadiyanto, Hadiyanto (CV. ULIL ALBAB CORP, 2025)
This study explores the acceptance and usage of ChatGPT among students in the Digital Communication and Media program at IPB University, specifically in assisting the completion of Content Analysis practical tasks. By employing the Technology Acceptance Model (TAM), the study investigates factors such as Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Toward Using (ATU), and Intention to Use (ITU) in relation to the actual use of ChatGPT. A survey was conducted among 17 students using a Likert scale questionnaire to gather data on their experiences. The results indicate that ChatGPT is highly regarded for its ability to assist in paraphrasing, content development, and deepening understanding of course materials, highlighting its perceived usefulness. Furthermore, the ease of access and use, especially across various devices, contributes to its positive reception. The study concludes that the adoption of ChatGPT by students is significantly influenced by its perceived utility and ease of use, which in turn drives their intention to use it more frequently for academic tasks, particularly in Content Analysis. These findings reinforce the relevance of TAM in understanding technology adoption in educational contexts.